How Does Learner-Centered Education Affect Madrasah Teachers' Pedagogic Competence? - Tambak, Syahraini; Sukenti, Desi; Hanafi, Yusuf; Rianawati, Rianawati; Amril, Amril (LPPM Undiksha, 2022)
Various studies illustrate that pedagogical competence is studied more psychologically in the learning process but has not revealed the strengthening of project-based learning in madrasa teacher learning. This study analyze whether increasing the use of project-based learning (PBL) by madrasah edago teachers in Indonesia improves the pedagogic competence of madrasah teachers in learning. This type of research is experimental and uses a quasi-experimental method. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative analysis, quantitative and statistical inferential. The subjects of this study are teachers from these madrasas who teach one of the four core subjects of Islamic religious education in total of 139 teachers. The result of the study is that the pedagogic competence of madrasah teachers is only considered a determinant of the teaching practice of Islamic religious education. However, we found that the pedagogic competence of madrasah teachers can be positively influenced by the increased use of PBL in learning. Among the madrasah teacher pedagogic competence subscales, PBL positively relates to student engagement and teaching and learning. Analysis using student data shows that students’ positive responses to Islamic religious education learning practices can mediate the relationship between PBL and the pedagogic competence of madrasa teachers. This research has implications for developing the PBL model in improving the pedagogic competence of madrasa teachers in learning Islamic religious education.